University and local recyclable material cooperative - Building bridges around e-waste - Fonseca, Janaina C. L.; Wendling Junior, Jose Marcelo [UNESP]; Eugenio, Gabriel R.; Milagre, Cintia D. F. (De Gruyter, 2024)
An e-waste outreach project was developed with two overriding goals: (1) to strengthen the partnership between the university and the local recyclable material cooperative, which has been carrying out actions aimed at supporting the work of the Cooperative, and (2) to collaborate in the expansion of environmental education activities in the process of social and economic insertion of collectors and the reduction of environmental impacts. During this process, the materials and corresponding activities related to the theoretical and practical course followed by the cooperative workers were developed by a transversal team of (under)graduate students, faculty, and staff from the Chemistry, Electric Engineering, and Public Administration areas. In addition, social media materials were created to sensibilize and engage the university community regarding effective e-waste awareness, to adhere to the voluntary drop-off point of e-waste collection, and to address the issues that can affect our environment and health if e-waste is sent to landfills. It was an example of how chemistry contributes to the Sustainable Development Goals through an outreach project.
Keywords: cooperativism; e-waste; outreach project; SDG #11; sustainability